An overview of patient acceptance of health information technology in developing countries: a review and conceptual model - Ahlan, Abdul Rahman; Ahmad, Barroon Isma'eel (SciKA, 2015)
The potential to improve the quality, efficiency, outcomes, patient safety and reduce cost of healthcare by Health Information Technology (HIT) has been established by researchers. But unfortunately HIT systems are not properly utilized or are not widely available. This problem is even more glaring in developing countries. This article presents a review of some available HIT systems in order to assess the level of their presence and the technology used in developing them. Works related to acceptance of HIT systems were also reviewed so as to study the gaps in this area and propose a solution in order to fill the gaps identified. The problems discovered from this review include lack of availability of these systems especially in developing countries, low rate of HIT systems acceptance and insufficient works on patient acceptance of HIT systems. Studying the factors that affect the acceptance of HIT systems by patients and considering the factors while developing the systems will play a significant role in getting over the aforementioned limitations. As Technology Acceptance Model (TAM) is one of the most popular models for studying users' perception and acceptance of Information System (IS)/Information Technology (IT), we proposed a conceptual model of HIT acceptance in developing countries based on TAM.